Carbon dioxide capture and storage (CCS): liability for non-permanence under the UNFCCC - Sven Bode; Martina Jung (Hamburg Institute of International Economics (HWWA), 2005)
Prior to CoP 10, our discussion paper ?On the Integration of Carbon Capture and Storage into the International Climate Regime? argued that carbon capture and storage (CCS) was similar to carbon sequestration in the area of Land Use, Land-Use Change and Forestry (LULUCF). This was criticized by several readers who observed that treating CCS as a removal activity (sink) would not be compatible with the UNFCCC sink definition, what we already had mentioned in the paper. The present paper is based on the UNFCCC definition and analyses how CCS could be integrated into the climate regime. As CO2 may re-enter the atmosphere after injection into geological reservoirs, the question of long-term liability has to be considered. Apart from this aspect, additional complexities arise from the fact that CO2 capture and storage can be carried out in two different countries. A classification of CCS cross-border activities shows that not all cases with non-Annex I participation fall under the CDM. Furthermore, we elaborate on the problem that seepage of CO2 from reservoirs located in non-Annex I countries – under current rules – would not be subtracted from the emission budget of any country. For these cases, solutions guaranteeing liability for possible non-permanence of CCS are proposed.
Keywords: Q25; Q40; Q28; 330; Carbon Dioxide Capture and Storage; CDM; Climate Change; UNFCCC; Luftverunreinigung; Kohlendioxid; Klimaschutz; Umwelttechnik